2013
DOI: 10.2478/pjvs-2013-0071
|View full text |Cite
|
Sign up to set email alerts
|

The influence of antibiotic treatment of bitches in oestrus on their attractiveness to males during mating

Abstract: The aim of this study was to evaluate the influence of the antibiotic treatment, including the mode of drugs administration, on bitches' attractiveness to the stud dogs during mating. Moreover, we tried to estimate the possibility of aversive effect of the drug vehicle on the male behavior. In experiment I, four bitches in oestrus without antibiotic treatment (group A), four bitches treated with intravaginal antibiotic (group B) and four bitches treated with intramuscular antibiotic (group C) were presented to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Intravaginal antibiotic treatment affects the genital microbiome, leading to dysbiosis. Bitches administrated antibiotics intravaginally during estrus were less likely to attract males when in estrus compared with females not treated with antibiotics ( Figure 1 ) [ 77 ]. The changes in the sexual behavior would be the result of changes in the microbial diversity and the semiochemical signal emitted by the modified microbiome because of the antibiotic treatment.…”
Section: Dysbiosis and Genital Microbiome Disruptionmentioning
confidence: 99%
“…Intravaginal antibiotic treatment affects the genital microbiome, leading to dysbiosis. Bitches administrated antibiotics intravaginally during estrus were less likely to attract males when in estrus compared with females not treated with antibiotics ( Figure 1 ) [ 77 ]. The changes in the sexual behavior would be the result of changes in the microbial diversity and the semiochemical signal emitted by the modified microbiome because of the antibiotic treatment.…”
Section: Dysbiosis and Genital Microbiome Disruptionmentioning
confidence: 99%
“…It is worth mentioning that inflammatory conditions like vulvovaginitis in females could be responsible for the increased interest of the male in some cases. What also seems to be important is that, according to the literature, the bacterial flora could be involved in the creation of the final semiochemical signal, thus its alteration could influence the composition of the VOCs emitted by the individual [ 44 , 45 , 46 ]. From the other side the inflammation by itself could be the reason for modification of the VOCs, for example, present in the urine, what was experimentally confirmed in the study of Gordon [ 47 ], in which the induced inflammatory process was the reason for appearance in the urine of the compounds usually not detectable there in humans.…”
Section: Discussionmentioning
confidence: 99%
“…It has been observed that some stud dogs can distinguish between particular phases of heat in bitches, and will attempt mating only with females that are at the so-called optimal time for mating—a behavior that some breeders used to use for identification of this period instead of using a laboratory test based on progesterone level determination [ 151 , 152 ]. Moreover, dogs were also able to detect changes in the odor of a female in estrus treated with antibiotics [ 153 ].…”
Section: Recognition Of the Physiological State By Olfactionmentioning
confidence: 99%